1993
DOI: 10.1111/j.1744-313x.1993.tb00144.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Caprine Leucocyte Class I and Ii Antigens in Saanen Goats Affected by Caprine Arthritis (Cae)

Abstract: The distribution of CLA class I and II antigens in CAE virus-infected, diseased and healthy Saanen goats has been investigated. Three class I antigens and two class II antigens showed a statistically different frequency in the two groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Further bias might have been introduced by selecting the smaller flocks in the extensive system and those registered with the local milk-board among intensive flocks, but it is unlikely that either factor contributes greatly to explaining the enormous differences in MVV-seroprevalence in these two sheep production systems. Moreover, although certain alleles have been identified that confer goats and cows some degree of resistance to lentiviral infections [19,29] and there are indications of inheritable susceptibility and resistance to MVVseroconversion in sheep [6], there is no evidence or previous suggestions, that major differences in flock MVV-seroprevalence are attributable to genetic differences between sheep. Breed-associated differences in susceptibility to infection have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Further bias might have been introduced by selecting the smaller flocks in the extensive system and those registered with the local milk-board among intensive flocks, but it is unlikely that either factor contributes greatly to explaining the enormous differences in MVV-seroprevalence in these two sheep production systems. Moreover, although certain alleles have been identified that confer goats and cows some degree of resistance to lentiviral infections [19,29] and there are indications of inheritable susceptibility and resistance to MVVseroconversion in sheep [6], there is no evidence or previous suggestions, that major differences in flock MVV-seroprevalence are attributable to genetic differences between sheep. Breed-associated differences in susceptibility to infection have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Economic losses are due to reduced milk yield, mastitis, interaction with bacterial mammary infection, and premature culling [22,23,24,25]. Importantly, both OvLV and CaLV show evidence of breed differences in susceptibility [26,27,28,29,30,31,32,33,34], that together with other evidence [35,36,37,38,39] suggest a host genetic component in susceptibility and control. …”
Section: Small Ruminant Lentiviruses: Background and Existing Intervmentioning
confidence: 99%
“…There was consensus that immunosuppression is not a feature of SRLV infection probably because, in contrast to the immunodeficiency-causing lentiviruses, SRLVs do not infect lymphocytes [16,53]. Genetic factors of both the host (breed-and familyassociated disease susceptibility) and the virus (virulence) influence the outcome of SRLV infection [36,123].…”
Section: Animal Welfare Consequencesmentioning
confidence: 99%